The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.isci.2020.101894
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analyses of the gill symbiosis of the bathymodiolin mussel Gigantidas platifrons

Abstract: Summary Although the deep-sea bathymodiolin mussels have been intensively studied as a model of animal-bacteria symbiosis, it remains challenging to assess the host-symbiont interactions due to the complexity of the symbiotic tissue—the gill. Using cold-seep mussel Gigantidas platifrons as a model, we isolated the symbiont harboring bacteriocytes and profiled the transcriptomes of the three major parts of the symbiosis—the gill, the bacteriocyte, and the symbiont. This breakdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 102 publications
2
18
0
Order By: Relevance
“…We observed a significant increase in Candidatus Vesicomyosocius in PA (PA relative abundance = 32.8%, NPA relative abundance = 1.63%, p = 0.0079) and Methyloprofundus (PA relative abundance = 16.9%, NPA relative abundance = 1.25%, p = 0.0043). The chemoautotrophic bacteria are considered symbionts that fix carbon dioxide, detoxify hydrogen sulfide, and provide their hosts with organic carbon compounds ( Wang et al, 2021 ). Endosymbiotic relationships with chemosynthetic bacteria have enabled many deep-sea invertebrates to flourish in hydrothermal vents and cold seeps ( Ip et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We observed a significant increase in Candidatus Vesicomyosocius in PA (PA relative abundance = 32.8%, NPA relative abundance = 1.63%, p = 0.0079) and Methyloprofundus (PA relative abundance = 16.9%, NPA relative abundance = 1.25%, p = 0.0043). The chemoautotrophic bacteria are considered symbionts that fix carbon dioxide, detoxify hydrogen sulfide, and provide their hosts with organic carbon compounds ( Wang et al, 2021 ). Endosymbiotic relationships with chemosynthetic bacteria have enabled many deep-sea invertebrates to flourish in hydrothermal vents and cold seeps ( Ip et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the previously reported genome and transcriptome information of G. platifrons , GpTLR13 was greatly expanded and highly expressed in gill tissue, implying its potential role in symbiosis ( Wong et al, 2015 ; Sun et al, 2017 ). Meanwhile, recent study reported that TLRs were significantly enriched in bacteriocyte transcriptomes in G. platifrons by profiling the transcriptomes of the gill, bacteriocyte, and symbiont, respectively, which confirmed the important role of TLRs in symbiosis ( Wang et al, 2021 ). Therefore, the molecular character and immune function of GpTLR13 were further analyzed to address its role in symbiosis.…”
Section: Discussionmentioning
confidence: 67%
“…The in situ hybridization assay (ISH) was conducted as previously described (50). For the verification of cell types, cell markers were cloned with gene-specific primers to synthesize the digoxigenin labelled ISH probes.…”
Section: Methodsmentioning
confidence: 99%